Reimagining ageing: insights from teaching co-design methods with designers, seniors and industry partners. Issue 1 (2nd January 2018) - Taffe, Simone; Pedell, Sonja; Wilkinson, Andrea
ABSTRACT: Interest in co-design is growing in the design literature, as is problem-based learning in design education, yet little research exists on teaching co-design in collaboration with industry partners. This leaves design educators wondering 'what is the influence of teaching co-design with actual industry partners on student learning?' This study discusses a case study where two industry partners were invited to collaborate with seniors and multi-discipline design students to redefine ageing. Both projects involved co-designing future assistive technologies. The results demonstrate that when design students and seniors co-designed prototypes to de-stigmatize images of ageing, the results delighted our end-users. The findings suggest combining co-design methods with health-related industry briefs offers an immersive environment for design students to learn and apply creative strategies to propose novel designs, in new complex domains. As designers are not experts in health, co-design methods give designers tools to leverage expert end-user knowledge to produce innovative, high impact designs – hence opening up new work domains.